The politics of higher education: university President ideology and external networking - Rabovsky, Thomas; Rutherford, Amanda (2016)
While the importance of networking is increasingly recognized by practitioners and scholars alike, little is known about why significant variance is observed in how often and with whom organizational leaders network. Further, while we know that political ideology plays a critical role in shaping decision making within public organizations, current models of networking have largely failed to consider the importance of ideology in driving networking efforts. Using data from a 2012 survey of U.S. university presidents and the Integrated Postsecondary Education Data System, this article explores the role that president ideology plays in shaping networking behavior with political principals. Findings suggest that the effect of ideology on external networking efforts is moderated by state policy maker ideology. - Reproduced.
Keywords: Higher Education